FIRST-PRINCIPLES STUDY OF NANOTUBE- BASED GASES SENSORS FOR O2, CL2, F2 AND CO DETECTION: DFT/B3LYP INVESTIGATIONS - Irzooqi, Wisam Shareef (Journal for Technology and Science, 2026)
Objective: This study examines the sensing potential of carbon nanotubes (CNTs) for the adsorption of F2, O2, CL2, and CO molecules. Method: Investigations were conducted on the electronic properties, adsorption energy, and geometry optimization. The density functional theory at the B3LYP/631G level using the Gaussian 09W software package serves as the foundation for all of the computations. Results: The distance between the CNTS and CL2, O2, F2, and CO molecules determines the adsorption process. All of the structures also have different levels of chemical hardness and electron affinity. This indicates that, for such structures to be cations or anions, a higher energy was required to donate or accept an electron. The usage of CNTS as a nanosensor is confirmed by this study. Novelty: Because of their special properties, Carbon Nanotube (CNTs) have drawn a lot of attention. A variety of devices, including nanosensors, could make use of such CNTS properties. High sensitivity to unique gas molecules and quick response times make CNTS nanosensors ideal for critical applications. Recently, the theoretical investigation regarding gas adsorption across the outer surface of CNTS nanosensors has been deemed quite intriguing.